Medium raw a bloody valentine to the world of food and the people who cook - Bourdain, Anthony (New York, NY Ecco Press, 2010)
Tracking his own strange and unexpected voyage from journeyman cook to globe-traveling professional eater and drinker, and even to fatherhood, Bourdain takes no prisoners as he dissects what he's seen, pausing along the way for a series of confessions, rants, investigations, and interrogations of some of the most controversial figures in food.
Selling out -- The happy ending -- The rich eat differently than you and me -- I drink alone -- So you wanna be a chef -- Virtue -- The fear -- Lust -- Meat -- Lower education -- I'm dancing -- "Go ask Alice" -- Heroes and villains -- Alan Richman is a douchebag -- "I lost on Top Chef" -- "It's not you, it's me" -- The fury -- My aim is true -- The fish-on-Monday thing.
Keywords: Bourdain, Anthony; Gastronomy; Cooks -- New York (State) -- New York -- Biography